Das aufstrebende Berufsbild des Data Scientist: Vom Kompetenzwirrwarr zu spezifischen Anforderungsprofilen - Schumann, Conny; Zschech, Patrick; Hilbert, Andreas (HMD : Praxis der Wirtschaftsinformatik, 2016)
To transform the variety of heterogeneous data streams into enterprise decision-relevant information, not just modern business analytics approaches have been developed in recent years. In addition, a new job profile called for attention within the rising era of Big Data: the Data Scientist. The variety of skills that come along with this new profession has been described in various technical papers and is now summarized in this article through a systematic literature review. For this purpose, the identified competences are not only enumerated, but also classified within a competency model using a content analysis. The result of this examination is that according to the literature a Data Scientist should provide an extensive skill set – including professional skills such as statistics or KDD-relevant skills for the selection, preprocessing, analysis and interpretation of data, but also social skills such as teamwork and communication, as well as personal skills such as curiosity or creativity. Here it becomes evident that a Data Scientist alone cannot meet all these competencies. Rather, it requires individual types of Data Scientists with different major focus depending on the roles and duties within the enterprise. For this purpose the article provides recommendations for the development of specific Data Scientist profiles based on the results of the literature and content analysis.<br
Keywords: Data Science; Kompetenzprofil; Handlungskompetenz; Business Analytics; Knowledge Discovery in Databases (KDD); Big Data